1995
DOI: 10.1016/s0741-5214(95)70030-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited range of motion is a significant factor in venous ulceration

Abstract: Limbs with CVI have a limited ankle ROM that decreases with increasing severity of clinical symptoms. This decreased ROM is associated with, and may contribute to, poor calf pump function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 12 publications
7
113
1
6
Order By: Relevance
“…Comprehensive evaluation and therapeutic management of these patients are less than expected [12][13][14][15] . The tibiotarsal joint mobility combined with venous valvular competence, working simultaneously, is the engine that drives the return of venous blood to the heart via anatomical relations between nerves, muscles, tendons, joint capsules, ligaments and cartilages 16 . We observed that the reduction of ROM is an aggravating factor for CVI of lower limbs, because total and permanent ankle ankylosis makes patients incurable by limiting, or even annulling, the most important action of the pulse-aspiration pump of lower limbs, which is the calf muscle 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive evaluation and therapeutic management of these patients are less than expected [12][13][14][15] . The tibiotarsal joint mobility combined with venous valvular competence, working simultaneously, is the engine that drives the return of venous blood to the heart via anatomical relations between nerves, muscles, tendons, joint capsules, ligaments and cartilages 16 . We observed that the reduction of ROM is an aggravating factor for CVI of lower limbs, because total and permanent ankle ankylosis makes patients incurable by limiting, or even annulling, the most important action of the pulse-aspiration pump of lower limbs, which is the calf muscle 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Back et al stated that a normal walking motion is required for activation of the calf muscular pump and this requires 90 degrees of dorsiflexion [78]. It has been found that exercise program twice a week increased the angle of dorsiflexion and plantar flexion in those with CVI [79].…”
Section: Exercisementioning
confidence: 99%
“…Calf muscle pump dysfunction might be caused by weakness of calf muscles but may also be related to decreased range of motion around the ankle joint during walking and other movements [30,75,78,98], neuropathy, muscle denervation or muscle atrophy, or gait abnormalities [29,36,43].…”
Section: Impairment Of Calf Muscle Pump and Functional Capacitymentioning
confidence: 99%